The portal vein‐variceal anastomosis: an important technique for establishing portal vein inflow. (21st November 2013) - Alexopoulos, Sophoclis P.; Thomas, Elizabeth; Berry, Emily; Whang, Gilbert; Matsuoka, Lea
Abstract Background Adequate portal vein inflow is critical to successful orthotopic liver transplantation. While an end‐to‐end donor to recipient portal vein anastomosis is fashioned in the majority of liver transplant recipients, approximately 2% of recipients will require a complex vascular reconstruction due to inadequate recipient portal vein inflow. In this series, we describe our experience with five patients in which porto‐variceal anastomosis was used to treat extensive porto‐mesenteric thrombosis. Methods Charts for patients who underwent liver transplantation from January 1, 2006, to December 31, 2011, were reviewed for patients requiring porto‐variceal anastomosis. Results Five patients had extensive porto‐splenomesenteric thrombosis requiring utilization of a varix as portal inflow. An iliac vein graft was utilized in four patients, and a direct anastomosis was performed in one patient. The patient with the direct anastomosis required revision with the use of an iliac vein graft the following day. Follow‐up imaging documented portal vein patency at a minimum of three months post‐transplant. No patients suffered post‐operative variceal hemorrhage and all five patients are alive with a functional primary graft at a median follow‐up of 2.3 yr. Conclusions A porto‐variceal anastomosis should be feasible in the majority of patients with extensive porto‐mesenteric thrombosis with excellent durability.